Competencias profesionales para la atención de las dificultades en la lecto-escritura de los estudiantes de educación general básica media - Rosado Coello, Inés Maribel (2021)
The present research delves into the analysis of the insufficient development of professional competences that teachers have, a situation that limits the progress of literacy in students with difficulties in this field. To verify the problem and design the proposal, a methodology with a mixed, descriptive and field approach was used, for this, the bibliographic search, the application of methods and techniques of the empirical level was used: interview, observation and survey. The study population was the seventh year of basic education of the Juan Javier Espinoza Fiscal Education Unit and the sample was constituted by the student group with learning difficulties in reading and writing. To help solve this problem, a series of pedagogical training workshops for teachers was designed. Regarding the validation of the proposal entitled: Pedagogical workshops for the improvement of professional competences related to the attention to the difficulties in reading and writing in secondary basic education, the experts confirmed the effectiveness and relevance. Finally, it is concluded that the theoretical, conceptual and legal assumptions valued and assumed in the research connote its importance in Ecuador and particularly in the school context.............